2005
DOI: 10.2133/dmpk.20.268
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Culture Conditions on CYP3A4 and MDR1 mRNA Induction by 1α,25-Dihydroxyvitamin D3 in Human Intestinal Cell Lines, Caco-2 and LS180†

Abstract: To evaluate an in vitro model suitable for investigating intestinal first-pass drug metabolism, CYP3A4 and MDR1 mRNA induction by 1alpha,25-dihydroxyvitamin D(3) (VD3) was examined in two human intestinal cell lines, Caco-2 and LS180, under various culture conditions. CYP3A4 mRNA expression was induced by 100 nM VD3 at levels between 234-549 times above normal in Caco-2 cells for 2 weeks and by 74-200 times above normal in LS180 cells for 2 days. The CYP3A4 induction effect of 250 nM VD3 was similar to or slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…One of them is the drug efflux pump multi-drug resistance protein (MDR)-1, which is located in the enterocyte apical membrane (Pfrunder et al 2003, Aiba et al 2005). 1,25(OH) 2 D 3 also modulates the expression of members of the multi-drug resistanceassociated protein (MRP) family, which are involved in the transport of conjugated and unconjugated bile acids, and also in that of glutathione and sulphate conjugates (McCarthy et al 2005).…”
Section: Angiogenesismentioning
confidence: 99%
“…One of them is the drug efflux pump multi-drug resistance protein (MDR)-1, which is located in the enterocyte apical membrane (Pfrunder et al 2003, Aiba et al 2005). 1,25(OH) 2 D 3 also modulates the expression of members of the multi-drug resistanceassociated protein (MRP) family, which are involved in the transport of conjugated and unconjugated bile acids, and also in that of glutathione and sulphate conjugates (McCarthy et al 2005).…”
Section: Angiogenesismentioning
confidence: 99%
“…26) Recently, Caco-2 cells treated with VD 3 have been utilized to investigate intestinal drug metabolism by CYP3A4. 11,19) That is, we previously reported that the expression level of CYP3A4 mRNA in Caco-2 cells treated with 250 nM VD 3 was more than 300-fold higher than that in non-treated cells. 11) In fact, Schmiedlin-Ren et al reported that midazolam was metabolized significantly in Caco-2 cells treated with VD 3 .…”
Section: Resultsmentioning
confidence: 96%
“…Treatment of Caco-2 cells with b-NF and VD 3 induces UGTs and CYP3A4, respectively. 11,14,15,19,20) We, therefore, also evaluated changes in the metabolic rate of Rand S-carvedilol in b-NF-and VD 3 -treated Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations